PREVENTIVE MEASURES FOR THE PREVENTION OF METABOLIC SYNDROME AMONG SCHOOL STUDENTS (The Conference Hub, 2025)
The fact that the deviation from the daily routine among children and adolescents, the consumption of excess carbohydrates in the daily diet, the level of consumption of phosphates, dyes and sugary drinks in school conditions, the incorrect distribution of excess time, and the creation of conditions for the development of abdominal obesity and its complications have been documented in the works of a number of authors [1,2,3,4].In the conditions of the new Uzbekistan, the development of measures aimed at improving the health of schoolchildren and preventing metabolic syndrome is one of the urgent problems facing professionals in the field today.